1999
DOI: 10.1093/ps/78.8.1184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pelleting temperature on the recovery and efficacy of a xylanase enzyme in wheat-based diets

Abstract: Two trials were performed to test the stability and efficacy of a commercial enzyme preparation containing xylanase and protease activities to pelleting. In Trial 1, 576 male Cobb chicks were fed wheat-based diets to 21 d with or without enzyme and pelleted after conditioning for 55 or 140 s at 70, 75, 80, 85, 90, or 95 C. In Trial 2, 2,880 male Cobb chicks were fed wheat-based diets to 42 d with no enzyme, or with enzyme addition before or after pelleting with conditioning for 30 s at 70, 80, 90, or 95 C. Enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 13 publications
3
46
1
Order By: Relevance
“…It is reported that the endogenous enzymes in wheat grain, such as xylanase, are heat labile (Amerah 2015), which may affect their importance in broiler nutrition. Besides, overheating can result in the resistance of protein and starch to digestion (Silversides and Bedford 1999) and increased intestinal viscosity in broiler chickens (Gracia et al 2003). Therefore, in the present experiment, inactivation of endogenous enzymes in the heat treatment may be the reason for the reduction in growth performance in broilers compared to those that received microwave-treated diet.…”
Section: Discussionmentioning
confidence: 75%
“…It is reported that the endogenous enzymes in wheat grain, such as xylanase, are heat labile (Amerah 2015), which may affect their importance in broiler nutrition. Besides, overheating can result in the resistance of protein and starch to digestion (Silversides and Bedford 1999) and increased intestinal viscosity in broiler chickens (Gracia et al 2003). Therefore, in the present experiment, inactivation of endogenous enzymes in the heat treatment may be the reason for the reduction in growth performance in broilers compared to those that received microwave-treated diet.…”
Section: Discussionmentioning
confidence: 75%
“…In many trials these enzymes are shown to be effective in improving performance (for example, in broilers, Silversides and Bedford, 1999). However, as far as the authors are aware, very few trials of such enzymes have been conducted and published with a control in place that is supplemented only with single component xylanase.…”
Section: Ameliorating the Anti-nutritive Effectmentioning
confidence: 99%
“…The effect of exogenous enzymes on broiler mortality is equivocal. Some researchers have reported reduced mortality with enzyme supplementation [25,34], and others have reported no effect on mortality [35][36][37]. in general, the response to enzyme addition on mortality may be related to dietary or environmental stressors, such that exogenous enzymes reduce mortality only when basal mortality is sufficiently high.…”
Section: Finisher Phase Broiler Performancementioning
confidence: 99%